THE CONTESTATION OF SEXUAL VIOLENCE DISCOURSE IN INDONESIAN STATE ISLAMIC HIGHER EDUCATION INSTITUTIONS: A GENDER COMMUNICATION ANALYSIS - Marhamah; Hartini Mudarsa; Fauzi Fauzi; Shafira Ulfa Rahmani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
The contestation of sexual violence discourse within State Islamic Higher Education Institutions (PTKIN) in Indonesia reflects tensions between gender equality, religious values, and institutional authority. This study aims to examine how sexual violence discourse is contested within PTKIN and how gendered power relations, religious values, and institutional interests shape communication practices surrounding prevention and response mechanisms. Employing a qualitative descriptive approach, the research draws on data collected through interviews, observations, and analyses of online news and institutional documents. The findings reveal three interconnected forms of discourse contestation: the operation of gendered power relations in defining sexual violence, communicative silencing that constrains victims’ voices and reporting practices, and competing narratives surrounding prevention and response mechanisms. These contestations demonstrate that sexual violence is not merely a legal or ethical issue but also a communicative and ideological arena in which progressive and conservative interpretations of gender, religion, and institutional responsibility compete for legitimacy. The study contributes to communication scholarship by conceptualizing sexual violence discourse as a site where gendered power relations, religious authority, and organizational interests intersect and shape institutional responses. Its novelty lies in offering a contextual understanding of discourse formation within Islamic higher education, thereby extending gender communication studies beyond conventional legal and policy-centered approaches.